In vitro identification and Antifungal susceptibility of different Candida Species isolated from patients with or without Diabetes having Chronic Periodontitis - Deepti Chaurasia; Mukesh Gupta; eena Kulshrestha; Jyant Biswas; Smita D Dutta; Chandan Kumar Matsyapal; Neha Sharma (Occupational Health and Safety Society of Nepal, 2015)
Background: Candida albicans is the commonly associated species with oral lesions, but other Candida spp., such as C. glabrata, C. tropicalis, C. parapsilosis, C. krusei, and C. dubliniensis have also been isolated from the human saliva, even irrespective to the oral candidiasis. Candidal colonization has also been documented from subgingival plaque of adults with periodontitis. Objective: Nowadays there is a great demand of natural herbal medicines. For a Diabetic person having Periodontitis, the use antifungal drugs are must. Therefore the antifungal capacity of the commonly used drug and herbs has been evaluated. Methods: For the study, the patients were screened and categorised into two study and one control group, having 20 patients in each group, on the basis of their respective Blood Glucose level and Dental status using standard clinical parameters. Oral rinse of 60 patients including both gender were selected from the Out Patient Department of Periodontitis, Rungta College of Dental Sciences and Research, Chhattisgarh. Chrome Candida Agar Media was used to identify Candida albicans and NAC. In vitro tests of the effectiveness of selected antimycotic agents against test candidal isolates recovered from the patient were performed to check the efficacy of the antifungal agents by the Kirby-Bauer Disc Diffusion method. Result: We found that by the use of this chromogenic media most of the commonly recovered NAC can be easily distinguished as each species produced the widest range of colours and morphologies. The herbal extracts Aloe Vera and Garlic failed to inhibit the growth of the candidal species but Neem, Meetha Neem, Triphala, Tulsi showed sensitivity to varying degree. Now a day there are much popularity of using herbal products, having its extracts incorporated in the cosmetics and other products used by humans. Conclusion: We conducted the sensitivity check of the candidal isolates against the dental dentrifices and found that however all the toothpastes contained herbal extracts capable of destroying bacteria but it did not showed good results against candidal species except the Patanjali Toothpaste. This may be due the fact that Patanjali Dant Kanti Dental Cream has the combination of all the herbal extract mixed altogether.